Endurance training: Using the six minute time trial as the foundation for endurance training - Jilka, B. (Techniques Magazine, 2012)
A few years ago the author began searching for a simple test he could use to assess the current running ability of all his distance runners (800 - 5000 meters) and use the results to establish personalized training paces. The relative accuracy of the results was important to him; however it was also important that the test be easy to use throughout the season and that his athletes would be motivated by the results. So after hours of research, he came across a book written by Dr. Owen Anderson (Anderson, 2006) called Lactate Lift-Off. Through this research, and specifically Lactate Lift-Off, the author of this article found great details on how to utilize field-testing methods (vs. a lab setting) to assess an athlete`s ability and then create workouts that lead to improved running economy. Based upon this research, the test he has incorporated into his training philosophy is the six-minute time trial. From an individual time trial result, he can determine a runner`s vVO2max (velocity at VO2max) and establish reliable training paces that: 1) allow him to create training plans and workouts that adhere to the well established Principles of Training, and 2) stimulate the body`s energy and neuromuscular systems to maximize training - and therefore improve running economy.